Measured Versus Estimated Resting Metabolic Rate in Heart Failure With Preserved Ejection Fraction. (4th August 2021) - Anderson, Theresa; Cascino, Thomas M.; Koelling, Todd M.; Perry, Daniel; Grafton, Gillian; Houston, Denise K.; Upadhya, Bharathi; Kitzman, Dalane W.; Hummel, Scott L.
Abstract : Background: Obesity is common in heart failure with preserved ejection fraction (HFpEF), and a hypocaloric diet can improve functional capacity. Malnutrition, sarcopenia, and frailty are also frequently present, and calorie restriction could harm some patients. Resting metabolic rate (RMR) is an essential determinant of caloric needs; however, it is rarely measured in clinical practice. The accuracy of commonly used predictive equations in HFpEF is unknown. Methods: RMR was measured with indirect calorimetry in 43 patients with HFpEF undergoing right heart catheterization at the University of Michigan, and among 49 participants in the SECRET trial (Study of the Effects of Caloric Restriction and Exercise Training in Patients With Heart Failure and a Normal Ejection Fraction); SECRET patients also had dual-energy X-ray absorptiometry body composition measures. Measured RMR was compared with RMR estimated using the Harris Benedict, Mifflin-St Jeor, World Health Organization, and Academy for Nutrition and Dietetics equations. Results: All predictive equations overestimated RMR (by >10%, P <0.001 for all), with mean (95% CI) differences Harris Benedict equation +250 (186–313), Mifflin-St. Jeor equation +169 (110–229), World Health Organization equation +300 (239–361), and Academy for Nutrition and Dietetics equation +794 (890–697) kcal/day. Results were similar across both patient groups, and the discrepancy between measured and estimated RMR tended to increase with body mass index. In SECRET, measured RMR was closely associated with lean body mass (ρ=0.74; by linear regression adjusted for age and sex: β=27 [95% CI, 18–36] kcal/day per kg, P <0.001; r 2 =0.56). Conclusions: Commonly used predictive equations systematically overestimate measured RMR in patients with HFpEF. Direct measurement of RMR may be needed to effectively tailor dietary guidance in this population. Registration: URL: https://www.clinicaltrials.gov ; Unique Identifier: NCT00959660.